Раннеэоплейстоценовые корнезубые полевки из Забайкалья - Ербаева, М.А. (Вестник зоологии, 1976)
Two fossil voles, Villanyia eleonorae sp. nov. and Mimomys minor Feif a r, from the Early Eopieistocene deposits in the Transbaikal area are described. Mimomys minor was described from the Villa-Frasnian deposits in Czechoslovakia. Villanyia eleonorae sp. nov. resembles Villanyia petenyi which is described from deposits of Hungary and the Ukraine. The type is at the Zoological Institute of the Academy of Sciences of the USSR, Leningrad.